Determination of oxytetracycline hydrochloride in milk and egg white samples using Ru(bipy)32+–Ce(SO4)2 chemiluminescence. (5th February 2019) - Xing‐yu, Long; Jiang‐ning, Gong; Mao, Deng; Di, Wu; Zhuo, Chen; Pin‐hua, Xia; Xiao‐jian, Gong; Qin, Deng; Zhi‐hui, Shi; Xue‐mei, Yan; Ru‐qing, Tian; Cai‐yun, Jiang
Abstract: A novel, rapid and sensitive chemiluminescence (CL) method for the determination of oxytetracycline hydrochloride (OTCH) is described in this paper. The presented method was based on the fact that OTCH could immensely enhance the CL of the reaction of cerium sulfate and tris(2, 2‐bipyridyl) ruthenium (II) in acidic medium. Under optimal experimental conditions, CL intensity was favorably linear for OTCH in the range 5.0 × 10 −7 to 5.0 × 10 −5 g/ml, with a detection limit of 1.5 × 10 −7 g/ml ( S / N = 3). The relative standard detection was 4.76% for 5.0 × 10 −6 g/ml ( n = 11). This method was successfully applied to the analysis of OTCH in milk and egg white samples. According to the results of the kinetic curves for OTCH in the Ru(bipy)3 2+ –Ce(SO4 )2 CL system, together with CL and ultraviolet (UV)–visible spectra, the possible mechanism of the CL reaction is discussed briefly.